1.12-W Q-switched Yb:KGW laser based on transmission-type Bi2Se3 saturable absorber *Project supported by the National Basic Research Program of China (Grant No. 2013CB922404), the National Natural Science Foundation of China (Grant No. 61177047), and the Beijing Municipal Education Commission Project, China (Grant No. KM201010005007). (February 2015) - Liu 刘, Jing-Hui 京徽; Tian 田, Jin-Rong 金荣; Hu 胡, Meng-Ting 梦婷; Xu 徐, Run-Qin 润亲; Dou 窦, Zhi-Yuan 志远; Yu 于, Zhen-Hua 振华; Song 宋, Yan-Rong 晏蓉
Abstract: We present a passively Q-switched Yb:KGW laser based on a transmission-type saturable absorber of topological insulator: Bi2 Se3 . The saturable absorber is prepared on a 0.17-mm glass substrate and can translate intra-cavity for best performance nearly without influence on the laser mode. At a maximum pump power of 13.7 W, the central wavelength, pulse duration, repetition rate, and pulse energy of Q-switched pulse are 1043 nm, 1.5 μs, 175.4 kHz, 6.39 μJ, respectively. The maximum output power is 1.12 W. To our knowledge, this is the highest average output power from passively Q-switched lasers with topological insulator saturable absorbers.